2020
DOI: 10.1007/s13197-020-04641-w
|View full text |Cite
|
Sign up to set email alerts
|

Detecting mislabelling in meat products using PCR–FINS

Abstract: Economically motivated adulteration (EMA) or misrepresentation of meat products is of concern, especially in developing countries, due to obvious health hazards and religious sensitivities. As Indian cooking involves prolonged heat treatments and addition of spices and condiments, species authentication of food, especially meat products, may be challenging. This study evaluated the efficacy of Polymerase Chain Reaction-Forensically Informative Sequencing (PCR-FINS) in meat speciation of highly processed meat. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…The use of DNA barcoding may be limited in highly processed tuna products where DNA could be degraded into smaller fragments that are difficult to amplify [ 39 ]. However, Polymerase Chain Reaction-Forensically Informative Sequencing (PCR-FINS) and mini-DNA barcoding methods were successfully applied for species identification in highly processed meat foods [ 40 ] and in museum specimens [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of DNA barcoding may be limited in highly processed tuna products where DNA could be degraded into smaller fragments that are difficult to amplify [ 39 ]. However, Polymerase Chain Reaction-Forensically Informative Sequencing (PCR-FINS) and mini-DNA barcoding methods were successfully applied for species identification in highly processed meat foods [ 40 ] and in museum specimens [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study corroborates with Li et al, 2020 [26], and Zhang and Xue, 2016 [27], who identified artificial enhancement as the major food fraud type and was due to usage of unapproved veterinary and human drug residues, or chemicals such as pesticides, food additives, and veterinary that were beyond the approved limits to enhance or prolonged the shelf-life of the food and drink products. Species replacement has been identified as a major problem in meat and poultry products [36,37], seafood [38,39], tubers [40], with 20% to more than 70% of the sampled products in the reported studies were identified as different species compared to the commercial name indicated on the label.…”
Section: Discussionmentioning
confidence: 99%
“…Pengembangan metode yang lebih cepat dan akurat untuk mengidentifikasi spesies dalam komoditas pangan, seperti mendeteksi daging babi dalam makanan masih terus dilakukan. Berbagai metode analitik yang telah dikembangkan untuk identifikasi babi, diantaranya adalah metode berbasis lipid (Rohman et al, 2011;Stachniuk et al, 2021), metode berbasis protein/Enzyme-Linked Immunosorbent Assay (ELISA) (Adam et al, 2017;Mandli et al, 2018), dan metode berbasis DNA (Ali et al, 2012;Ha et al, 2017;Kim et al, 2016;Soman et al, 2020).…”
Section: Pendahuluanunclassified
“…Sejumlah pengembangan metode Polymerase Chain Reaction (PCR) yang akhir-akhir ini digunakan untuk identifikasi DNA babi, diantaranya adalah PCR-RFLP (Restriction Fragment Length Pholymorphism) (Ali et al, 2011a), spesies spesifik PCR (Hafidz et al, 2020); realtime PCR menggunakan probe spesifik dengan target gen Cyt B (Ali et al, 2012), target D-loop (Kim et al, 2016); PCR -QIAxcel capillary electrophoresis system dengan target Cyt B dan D-loop (Barakat et al, 2014); serta PCR -Forensically Informative Sequencing (PCR-FINS) dengan target gen Cyt B dan ATP synthase (Soman et al, 2020).…”
Section: Pendahuluanunclassified